Volume contracted state, mortality and functional outcomes in patients with acute ischaemic stroke due to large vessel occlusion - Risheng Xu; Max Wintermark; Gregory W Albers; Jeremy J Heit; Adam A Dmytriw; Adrien Guenego; Yasmin Aziz; Kambiz Nael; Benjamin Pulli; Victor Urrutia; Dhairya A Lakhani; Tobias D Faizy; et al. (BMJ Neurology Open)
Background Acute ischaemic stroke (AIS) is a leading cause of mortality and disability globally, with volume contracted state (VCS), as indicated by an elevated blood urea nitrogen to creatinine (BUN/Cr) ratio, potentially influencing outcomes. This study investigates the association between VCS and clinical outcomes in patients with AIS due to large vessel occlusion (LVO).Methods A retrospective cohort study was conducted involving 298 patients with LVO-AIS from two comprehensive stroke centres. Patients were divided into two groups based on BUN/Cr ratio: ≤20 (n=205) and >20 (n=93). Primary outcomes included 90-day mortality and unfavourable functional outcomes, defined as a modified Rankin Scale score of 3–6. Secondary outcomes included the successful reperfusion, haemorrhagic transformation and National Institutes of Health Stroke Scale score at discharge.Results Patients with a BUN/Cr ratio >20 had significantly higher 90-day mortality (35% vs 13%, p<0.001) and this association remained significant after adjusting for confounding factors (OR 2.20; 95% CI 1.11 to 4.39; p=0.024). However, VCS was not significantly associated with unfavourable functional outcomes at 90 days (OR 1.28; 95% CI 0.67 to 2.51; p=0.46). Age and initial stroke severity were more strongly associated with long-term functional outcomes.Conclusions VCS is associated with higher odds of 90-day mortality in patients with LVO-AIS but not with unfavourable functional outcomes. These findings suggest the need for further research into the role of hydration management in improving survival in patients with AIS, potentially informing future treatment protocols.